Contamination and washing of cloth masks and risk of infection among hospital health workers in Vietnam: a post hoc analysis of a randomised controlled trial - Abrar Ahmad Chughtai; Chandini Raina MacIntyre; Bayzidur Rahman; Holly Seale; Tham Chi Dung (BMJ Open)
Background In a previous randomised controlled trial (RCT) in hospital healthcare workers (HCWs), cloth masks resulted in a higher risk of respiratory infections compared with medical masks. This was the only published RCT of cloth masks at the time of the COVID-19 pandemic.Objective To do a post hoc analysis of unpublished data on mask washing and mask contamination from the original RCT to further understand poor performance of the two-layered cotton cloth mask used by HCWs in that RCT.Setting 14 secondary-level/tertiary-level hospitals in Hanoi, Vietnam.Participants A subgroup of 607 HCWs aged ≥18 years working full time in selected high-risk wards, who used a two-layered cloth mask and were part of a randomised controlled clinical trial comparing medical masks and cloth masks.Intervention Washing method for cloth masks (self-washing or hospital laundry). A substudy of contamination of a sample of 15 cloth and medical masks was also conducted.Outcome measure Infection rate over 4 weeks of follow up and viral contamination of masks tested by multiplex PCR.Results Viral contamination with rhinovirus was identified on both used medical and cloth masks. Most HCW (77% of daily washing) self-washed their masks by hand. The risk of infection was more than double among HCW self-washing their masks compared with the hospital laundry (HR 2.04 (95% CI 1.03 to 4.00); p=0.04). There was no significant difference in infection between HCW who wore cloth masks washed in the hospital laundry compared with medical masks (p=0.5).Conclusions Using self-reported method of washing, we showed double the risk of infection with seasonal respiratory viruses if masks were self-washed by hand by HCWs. The majority of HCWs in the study reported hand-washing their mask themselves. This could explain the poor performance of two layered cloth masks, if the self-washing was inadequate. Cloth masks washed in the hospital laundry were as protective as medical masks. Both cloth and medical masks were contaminated, but only cloth masks were reused in the study, reiterating the importance of daily washing of reusable cloth masks using proper method. A well-washed cloth mask can be as protective as a medical mask.Trial resgistration number ACTRN12610000887077.